Treatment and outcomes in patients with central nervous system metastases from breast cancer in the real-life ESME MBC cohort. (January 2020) - Pasquier, David; Darlix, Amélie; Louvel, Guillaume; Fraisse, Julien; Jacot, William; Brain, Etienne; Petit, Adeline; Mouret-Reynier, Marie Ange; Goncalves, Anthony; Dalenc, Florence; Deluche, Elise; Fresnel, Jean Sébastien; et al.
Abstract: Aim: The aims of the present study were to describe treatment patterns and survival outcomes in patients with central nervous system metastases (CNSM) selected among metastatic breast cancer (MBC) patients included in a retrospective study from the Epidemiological Strategy and Medical Economics (ESME) MBC cohort. Methods: Neurological progression-free survival (NPFS) and overall survival (OS) were estimated using the Kaplan–Meier method. Signiﬁcant contributors to NPFS were determined using a multivariate Cox proportional hazards model. Results: After a median follow-up of 42.8 months, of 16 701 patients included in the ESME MBC database, CNSM were diagnosed in 24.6% of patients. The most frequent treatments after diagnosis of CNSM were whole-brain radiotherapy (WBRT) (45.2%) and systemic treatment (59.3%). Median OS and NPFS were 7.9 months (95% CI: 7.2–8.4) and 5.5 months (95% CI: 5.2–5.8), respectively. In multivariate analysis, age >70 years (vs <50 years; HR = 1.40; 95% CI: 1.24–1.57), triple-negative tumours (vs HER2-/HR+; HR = 1.87; 95% CI: 1.71–2.06), HER2+/HR-tumours (vs HER2-/HR+; HR = 1.14; 95% CI: 1.02–1.27), ≥3 metastatic sites (vs < 3; HR = 1.32; 95% CI: 1.21–1.43) and ≥3 previous treatment lines (vs < 3; HR = 1.75; 95% CI: 1.56–1.96) were detrimental for NPFS. A time interval between selection and CNSM diagnosis superior to 18 months (vs <9 months; HR = 0.88; 95% CI: 0.78–0.98) was associated with longer NPFS. Conclusions: This study describes current treatment patterns of MBC patients in a "real life" setting. Despite advances in stereotactic radiation therapy, most of the patients still received WBRT. More research is warranted to identify patient subsets for tailored treatment strategies. Highlights: We present treatment and outcomes in 4118 patients with central nervous system metastases (CNSM) from breast cancer. Despite advances in stereotactic radiotherapy, most patients received whole-brain radiotherapy. Neurological progression-free survival was associated with several patient and treatment related factors.